2013
DOI: 10.1190/geo2012-0431.1
|View full text |Cite
|
Sign up to set email alerts
|

Organic maturity, elastic properties, and textural characteristics of self resourcing reservoirs

Abstract: Organic-rich rocks have long been recognized as source rocks for clastic reservoirs, but more recently they have gained importance as reservoirs. However, the processes of kerogen maturation and hydrocarbon transport and storage are still poorly understood. Some empirical relations have been developed to relate the increase in elastic modulus with increasing maturity. A systematic study of the cause for this increase in elastic modulus is still lacking, and information about seismic and mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…The mean Young's moduli obtained in these nanoindentation experiments decreased with maturity. Zargari et al (2013) explained this by suggesting that bitumen expelled during pyrolysis has lower moduli than kerogen. Uvarova et al (2014) studied variations in chemical composition and microstructure of organic-rich Kimmeridge Shale with a TOC content of 23%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean Young's moduli obtained in these nanoindentation experiments decreased with maturity. Zargari et al (2013) explained this by suggesting that bitumen expelled during pyrolysis has lower moduli than kerogen. Uvarova et al (2014) studied variations in chemical composition and microstructure of organic-rich Kimmeridge Shale with a TOC content of 23%.…”
Section: Introductionmentioning
confidence: 99%
“…To understand relations between thermal maturation and microstructural changes, Zargari et al (2013) measured the distribution of Young's moduli on the surfaces of natural samples at different maturity levels and of samples subjected to the hydrous pyrolysis process. The mean Young's moduli obtained in these nanoindentation experiments decreased with maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Most void (pore-fractures) space is saturated by fluids, including hydrocarbon and the formation of water, of which hydrocarbon may be the softest part within the MS rocks. Zargari et al (2013) reported that extruded bitumen exhibit Young's modulus values as low as 2 GPa. In this study, residual hydrocarbon was extracted through the use of trichloromethane.…”
Section: Organic Mattermentioning
confidence: 99%
“…As proposed in previous works, the dynamic Young's modulus calculated by acoustic velocities also needs to be converted into the static Young's modulus based on the relationships between the two Young's moduli (Eissa and Kazi, 1988). Recently, some researchers have investigated the nano-micron mechanical properties of shale by using nanoindentation (Ulm and Abousleiman, 2006;Bobko and Ulm, 2008;Ahmadov et al, 2009;Zargari et al, 2013) and atomic force microscopy (AFM) techniques (Trtik et al, 2012;Eliyahu et al, 2015). To date, the factors impacting the MS elastic property have been revealed, primarily including micro/macro-structures (Josh et al, 2012), inorganic mineralogical composition (Mondol et al, 2007;Ding et al, 2012;Eliyahu et al, 2015), organic matter (Eliyahu et al, 2015), fluid media (Valès et al, 2004;Al-Bazali et al, 2008a;Abousleiman et al, 2010;Zhang et al, 2012b), confining stress (Sarout et al, 2007;Abousleiman et al, 2010), strain rate (Cook et al, 1990;Al-Bazali et al, 2008b), temperature (Masri et al, 2014), pore pressure (Al-Bazali et al, 2008b), porosity (Lashkaripour, 2002;Mondol et al, 2007), as well as others.…”
Section: Introductionmentioning
confidence: 99%
“…One of the sources of complexity in organic-rich shales is the intricate interplay between micro-texture evolution and kerogen maturity [1,18,20,23,24]. There is increasing evidence that the maturation of organic matter changes the micro-texture of organic-rich shales [18-20, 23, 25] contributing to the changes in mechanical properties of the rock.…”
Section: Introductionmentioning
confidence: 99%